MENSTRUAL POVERTY AND ITS IMPACTS ON WOMEN’S HEALTH: AN INTEGRATIVE REVIEW - Eduarda Almeida de Souza, Cicera; Gonçalves de Sousa, Rosyely; Cristina Alves da Silva Lima, Hellen; Henrique de Sousa Ribeiro, José; Denilson Aurélio Soares, Cicero; Duarte Santana, Jackson; Aguiar Tomé da Silva, Irlla; Faustino Sarmento, Samara; Faustino Sarmento, Silmara; do Nascimento Andrade Feitosa, Ankilma (Health and Society, 2022)
Introduction: The menstrual cycle is an indicator of female fertility and health. Menstruation is part of a woman’s reproductive cycle and happens every month due to shedding of the inner walls of the uterus when fertilization does not occur. During this time, women need basic products to maintain good hygiene. Lack of access to personal hygiene resources, infrastructure and even information about menstruation itself are the main characteristics of menstrual poverty. Objective: To identify in the literature the difficulty of women to have access to their menstrual rights and the impact of menstrual poverty on their health. Methodology: The present study refers to an integrative literature review, of a descriptive-exploratory nature, carried out from the bibliographic survey in the scientific databases SCIELO, MEDLINE and LILACS. Results and Discussions: In short, it was evidenced by the literature that menstruation is still fraught with sociocultural paradigms and taboos caused mainly by the lack of information. These dogmas are the main agents that interfere with women’s access to their menstrual rights. The consequence of this reality are the symptoms of dysmenorrhea, characterized by cramps, migraines and leg pain, factors that often interfere with school and work performance. Conclusion: The objective of the present study was achieved, allowing to demonstrate that there are diseases caused by menstrual poverty. In the trajectory of the analysis of this study, it was also possible to perceive that the lack of knowledge about female menstruation intensifies even more in the existing paradigms and taboos.